Timing of Antenatal Corticosteroid Administration in Monoamniotic Twins - Bibbo, Carolina (AJP Rep, 2019)
Objective  This study was aimed to determine if different strategies of antenatal corticosteroid (ACS) administration in monoamniotic twins leads to receipt within 7 days of delivery. Study Design  This is a retrospective cohort of monoamniotic twins managed at a single institution from 2007 to 2017. Patients were classified as to whether ACS were administered upon admission or at a predetermined gestational age (grouped together as “routine”) or for a change in clinical status (“indicated”). We used univariate analyses to associate ACS administration strategies with our primary outcome: receipt of ACS within 7 days of delivery. We then used generalized estimating equations to examine associations between fetal monitoring patterns and delivery within 1 week. Results  Twenty-four patients were included: eighteen patients in the “routine” group and six patients in the “indicated” group. There was no difference in optimal timing of ACS administration. Women experiencing delivery within the week were thrice more likely to spend on average more than 3 hours/day on the fetal monitor when compared with those who remained undelivered. Conclusion  Administration of ACS on admission is not effective. Fetal heart rate tracing surveillance might be a better methodology to predict delivery and guide ACS administration.